Activation of the HIF pathway in cancer. - Maxwell, P; Pugh, C; Ratcliffe, P (2001)
The maintenance of oxygen homeostasis is required both in physiological development and tumour growth. Hypoxia inducible factor (HIF) plays a central role in both processes. Reliable methods for visualising HIF alpha subunits have established that HIF activation occurs in the majority of common cancers. This occurs both by genetic mechanisms and through microenvironmental hypoxia. Activation of the HIF pathway has important effects on patterns of gene expression in tumours.